Neither Scale of Response Nor Threshold in Habitat Availability Is Conserved Across Species of Forest-Dwelling Songbirds Responding to Habitat Loss - Bill A. Thompson (Birds)
Thresholds can be an effective tool in conservation planning, as they can form a defensible target for habitat conservation or restoration. Generalized thresholds must be used with caution, however, as threshold responses may vary with species and spatial scale. The objectives of this study were to identify the scales at which forest-dwelling birds respond to both habitat availability and critical thresholds in forest cover associated with their occurrence, and to assess if life history traits relate to either scale of response or critical threshold. Using point count data from the Ontario Breeding Bird Atlas, I generated concentric buffers ranging from 100 m to 10 km radius around a random subset of point counts and described forest cover and species occurrence within each buffer. I assessed the likelihood of occurrence of each species at each scale of analysis using logistic regression and identified forest cover thresholds below which the occurrence of each species becomes unlikely using fitted regression curves and ROC plots. Species varied in their response to both landscape scale and forest cover, based on relative growth rate, clutch size, and site fidelity. The mean response to forest cover was 30.8%, with landscape scale ranging from 200 m to 9 km. Despite this range, pragmatic approaches to conservation planning are still possible.